2020
DOI: 10.3390/polym12051190
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Ultraviolet (UV)-Shielding Films Made from Waste Hemp Hurd and Polyvinyl Alcohol (PVA)

Abstract: This work proposes a new approach to fabricate highly transparent and flexible composite films that exhibit enhanced UV-shielding properties. Lignin has innate UV-shielding properties. However, when purified lignin, which is conventionally extracted through chemical treatment, is mixed with polymeric materials, its presence negatively influences the transparency of the resulting composite. High transparency and UV-shielding are desirable properties for many applications. In this study, composites were made by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 43 publications
5
35
0
Order By: Relevance
“…The analysis of the data showed that the treatments of the hemp shives did not cause significant structural variations, considering that only slight peak shifts towards higher 2θ angles related to the decrease of the interplanar distance of the cellulose’s planes, were observed. However, the intensity of the diffraction peak at 2θ ≈ 30° was increased after all treatments, which is in agreement with the data reported by Zhang et al [ 41 ]. This observation was interpreted by the lower preferential orientation of the cellulose fibers [ 37 ].…”
Section: Resultssupporting
confidence: 92%
“…The analysis of the data showed that the treatments of the hemp shives did not cause significant structural variations, considering that only slight peak shifts towards higher 2θ angles related to the decrease of the interplanar distance of the cellulose’s planes, were observed. However, the intensity of the diffraction peak at 2θ ≈ 30° was increased after all treatments, which is in agreement with the data reported by Zhang et al [ 41 ]. This observation was interpreted by the lower preferential orientation of the cellulose fibers [ 37 ].…”
Section: Resultssupporting
confidence: 92%
“…Hemp hurd particle (50 g) was wet ball-milled with an Attritor mill (2S, Union Process, USA) at an agitator speed of 280 rpm for 20 h, as reported before [10]. In our previous study with hemp hurd, we have intensively studied the influence of ball-milling time on the crystallinity of hemp [10].…”
Section: Fabrication Of Native Lignin-cellulose Nanocrystal (L-cncs)mentioning
confidence: 99%
“…Native lignin can be a better choice for light-coloured UV-shielding filler, as less chemical treatment is required. In our previous study [10], we obtained native lignin with the ball milling method. The light-coloured native lignin-cellulose was further added into the PVA matrix as a filler.…”
Section: Introductionmentioning
confidence: 99%
“…Fractured surfaces of stretch‐drawn samples were prepared by embedding with epoxy resin for 12 h and then frozen in liquid nitrogen. [ 16 ] Immediately after removal from the liquid nitrogen, samples were broken manually.…”
Section: Methodsmentioning
confidence: 99%